Penerapan Metode WP dan TOPSIS untuk Menentukan Unit Villa Sewa maupun Beli Berdasarkan Preferensi Pelanggan - Sahputra, Arfi Andi; Irawan, Muhammad Dedi (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2025)
The rapid growth of tourism in North Sumatra has increased the demand for accommodations, particularly villas. The abundance of villa choices often causes difficulties for tourists in selecting the most suitable option according to their preferences. This issue highlights the need for a Decision Support System (DSS) that can assist both customers and providers in making structured and objective decisions. This study aims to design a DSS for villa selection by applying the Weight Product (WP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods. The research steps include determining criteria, assigning weights, calculating preference values, and testing the results using both methods. WP recommended Villa Bukit Indah as the best option with a score of 0.2154, while TOPSIS identified Villa Block F–G as the best alternative with a score of 0.5811. Through the aggregation process, the final result showed that Villa Block F–G ranked first among five alternatives with the highest average score of 0.39145. The findings indicate that WP and TOPSIS can be applied complementarily to produce more accurate accommodation recommendations. Therefore, the proposed DSS supports companies in marketing strategies while helping customers choose villas that match their needs and preferences.Keywords - Customer Preference, Decision Support System, TOPSIS, Villa, Weight Product.